Kinetic Modelling of Liquid-Solid Extraction of Bioactive Compounds from Ginger Waste using Subcritical Water (Universitas Negeri Semarang, 2023)
Kinetic modelling played a key role in the development of subcritical water extraction for bioactive compounds such as: shogaol and gingerol from ginger waste. Liquid-solid extraction kinetics could predict the extraction phenomenon and increase the efficacy of extraction process. The aim of this study was to develop a mathematical model of leaching kinetics and determine the rate constant of extraction process (k) of shogaol and gingerol in ginger pulp which is in the subcritical water phase. The research was carried out in two work stages, namely modeling and experimentation. The modeling was done by comparing three extraction kinetic models, namely pseudo first order, pseudo second order and the distribution coefficient. The model was postulated and validated with experimental data using Matlab. The subcritical water extraction process of shogaol and gingerol in ginger waste was occurred at 140 ℃ with a pressure of 3.5 bar. The extracts had been separated from raffinate and further analyzed using HPLC-MS. The results showed that the pseudo first order kinetic model described well the phenomenon of subcritical water extraction with regression values was 0.9882 for gingerol and 0.9682 for shogaol respectively. The rate constant of extraction process (k) for gingerol and shogaol were 0.1101 and 0.3130 , respectively. This showed that the shogaol extraction rate was higher than the gingerol extraction rate.